2016
DOI: 10.1002/gcc.22420
|View full text |Cite
|
Sign up to set email alerts
|

Germline miRNA DNA variants and the risk of colorectal cancer by subtype

Abstract: MicroRNAs (miRNAs) regulate up to one‐third of all protein‐coding genes including genes relevant to cancer. Variants within miRNAs have been reported to be associated with prognosis, survival, response to chemotherapy across cancer types, in vitro parameters of cell growth, and altered risks for development of cancer. Five miRNA variants have been reported to be associated with risk for development of colorectal cancer (CRC). In this study, we evaluated germline genetic variation in 1,123 miRNAs in 899 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Noticeably, the GG genotype was associated with a high risk of CRC in males [ 23 ] and females [ 24 ] in two different Asian cohorts. According to our knowledge, there are nine other studies that found that rs2910164 was not related to CRC risk ( Table 1 ) [ 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Single Nucleotide Polymorphisms (Snps) In Genes For Mirnas Associated With Colorectal Cancer (Crc) Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, the GG genotype was associated with a high risk of CRC in males [ 23 ] and females [ 24 ] in two different Asian cohorts. According to our knowledge, there are nine other studies that found that rs2910164 was not related to CRC risk ( Table 1 ) [ 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Single Nucleotide Polymorphisms (Snps) In Genes For Mirnas Associated With Colorectal Cancer (Crc) Riskmentioning
confidence: 99%
“…Several studies link rs11614913 polymorphism with the risk of CRC [ 21 , 24 , 45 , 46 , 47 , 48 ]. On the other hand, 10 studies do not confirm this association [ 17 , 18 , 25 , 26 , 27 , 29 , 30 , 49 , 50 ].…”
Section: Single Nucleotide Polymorphisms (Snps) In Genes For Mirnas Associated With Colorectal Cancer (Crc) Riskmentioning
confidence: 99%
“…In addition, the dysregulation of miRNA is involved in numerous important steps of carcinogenesis, from initiation to metastasis . Recently, Lindor et al have shown that miR‐3191 was associated with CRC. In their study, germline genetic variations in 1123 miRNAs were analyzed from 899 CRC patients and 204 controls, and they identified 30 variants and 29 miRNAs associated with CRC, including miR‐3191.…”
Section: Introductionmentioning
confidence: 99%
“…NOS scores of the included studies were summarized in Table 5 . According to the criterion mentioned in previous study [ 42 , 43 ], we found that only two investigations were poor quality studies [ 36 , 44 ]. When we omitted these poor quality investigations, the findings were not changed.…”
Section: Resultsmentioning
confidence: 96%
“…The quality evaluation was used to improve the preent study. In the meta-analysis, we found that only two investigations were poor quality study [ 36 , 44 ]. In subgroup analysis, when we omitted them, the findings were not altered materially.…”
Section: Discussionmentioning
confidence: 99%